2024
DOI: 10.1186/s12889-024-18294-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of health rights accessibility on the urban integration of minority rural migrants in China: a cross-sectional study

Qingjun Zhao,
Guosong Wu,
Hanrui Wang

Abstract: Background Accessing health rights is an integral component of people’s aspirations for a better life. Existing discussions and evaluations regarding the accessibility of health rights for minority rural migrants are insufficient. In comparison to objective health conditions, inequalities in health rights lead to chronic and long-term depletion of human capital among minority rural migrants. This study aimed to assess the overall impact, heterogeneity effects, and mechanisms of health rights ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Furthermore, the positive association between the accessibility of health resources and psychological well-being has been theoretically and empirically confirmed [ 25 ]. A recent study found that health rights accessibility significantly enhances the psychological integration among minority rural migrants [ 26 ]. Therefore, the accessibility of health resources might mediate the association between hukou conversion and psychological integration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the positive association between the accessibility of health resources and psychological well-being has been theoretically and empirically confirmed [ 25 ]. A recent study found that health rights accessibility significantly enhances the psychological integration among minority rural migrants [ 26 ]. Therefore, the accessibility of health resources might mediate the association between hukou conversion and psychological integration.…”
Section: Introductionmentioning
confidence: 99%